ORGANIZATIONAL CULTURE DI PERGURUAN TINGGI (STUDI KASUS PADA SEKOLAH TINGGI ILMU EKONOMI YAPAN SURABAYA) - Handri Ardian Liputo (MAPAN: Jurnal Manajemen Akuntansi Palapa Nusantara, 2017)
Organizational culture is a shared meaning of nilai, beliefs, traditions, and organizational philosophy which members of the organization own, so, the organization is different  from  the  other  organizations.  Organizational  culture  that  members  feel  is  a quality, it’s supported by the shared meaning based on the value of helping each other. The quality of culture is supported by all tangible and intangible organization elements.